Cerebrospinal Fluid Parameters in Antisense Oligonucleotide-Treated Adult 5q-Spinal Muscular Atrophy Patients - Müschen, Lars Hendrik (Brain Sci, 2021)
Approval of nusinersen, an intrathecally administered antisense oligonucleotide, for the treatment of 5q-spinal muscular atrophy (SMA) marked the beginning of a new therapeutic era in neurological diseases. Changes in routine cerebrospinal fluid (CSF) parameters under nusinersen have only recently been described in adult SMA patients. We aimed to explore these findings in a real-world setting and to identify clinical and procedure-associated features that might impact CSF parameters. Routinely collected CSF parameters (leukocyte count, lactate, total protein, CSF/serum albumin quotient (QAlbumin), oligoclonal bands) of 28 adult SMA patients were examined for up to 22 months of nusinersen treatment. Total protein and QAlbumin values significantly increased in the first 10 months, independent of the administration procedure. By month 14, no further increases were detected. Two patients developed transient pleocytosis. In two cases, positive oligoclonal bands were found in the beginning and in four patients throughout the whole observation period. No clinical signs of inflammatory central nervous system disease were apparent. Our data confirm elevated CSF total protein and QAlbumin during nusinersen treatment. These alterations may be caused by both repeated lumbar punctures and the interval between procedures rather than by the medication itself. Generally, there were no severe alterations of CSF routine parameters. These results further underline the safety of nusinersen therapy.